Bank profitability and market concentration: Evidence from China - Yuan, Xiaojun (2022)
The purpose of this study is to examine the impact of comprehensive bank-specific and macroeconomic variables on bank performance, among which market concentration is a key variable of interest. The study further tests the hypothesis whether the impact of market concentration on bank profitability will depend on bank size and foreign ownership. A panel data of Chinese commercial banks is used in the statistical analysis, covering the period 2005-2020. System GMM estimator is employed because of its advantage in consistency and efficiency for estimating dynamic panel data. Results provide empirical evidence on several contributors in determining bank profitability: capitalization, cost management, liquidity and credit risks have significant impact on profitability; non-interest income ratio appear to be an insignificant variable; banks that possess better capitalization, more efficient cost management, higher degree of liquidity and better asset quality are more profitable than their counterparts. Turning to macroeconomic factors, using Herfindahl-Hirschman Index (HHI) as a measure of market concentration, the evidence indicates that concentration has positive effect on profitability for Chinese banks. Similar result is found on inflation rate but opposite for unemployment rate in the country. Finally, the result also shows that the positive effect of market concentration on profitability is enhanced for large banks than for others while the effect is decreased for foreign banks compared to domestic banks. This finding expands understanding on banking concentration condition in Chinese banking sector.